Determinants of Micro-Insurance Demand in Jimma Zone - Asmare, Aregu; Worku, Abel (International Research Journal of Business Studies, 2018)
Vulnerability to risk is a constant factor in the lives of the poor and a cause of persistent poverty. Microinsurance offers one approach to mitigate the risk, yet demand is relatively low in developing countries. Thus, the aim of this study was investigating determinants of microinsurance demand in Jimma Zone. The data used in this study was cross sectional which collected from households using structured questioner and in-depth interview with officials of insurance companies and microfinance institutions that provides microinsurance product. The collected data was analyzed using multinomial logistic regression model. The findings of the study show that household size, employment status, level of education, adequacy of micro-insurance supply, delivery channel, premium, monthly income, insurable asset, financial literacy, trust, and risk aversion has significant impact on the demand for microinsurance products, whereas age, gender, adverse selection and moral hazard, religion and peer influence has insignificant impact on household’s demand for microinsurance products.